OPTIMIZATION OF NANO SPRAY GEL FROM FERMENTED RED GINGER EXTRACT FOR ANTI-INFLAMMATORY - Ni Wayan Rika Kumara Dewi; Made Dwike Swari Santi; Ni Kadek Kintania Jenisca S.W. (Meditory : The Journal of Medical Laboratory, 2026)
Background: Red ginger contains bioactive compounds such as gingerol and shogaol with known anti-inflammatory activity, making it a potential active ingredient for nanospray gel formulations. Objective: This study aimed to optimize a nano spray gel formulation containing fermented red ginger extract using the Simplex Lattice Design (SLD). Methods: An experimental laboratory study was performed. Formulation optimization was conducted using Design-Expert® version 13 with the Simplex Lattice Design (SLD) approach by varying the concentrations of Carbopol 940, Triethanolamine (TEA), and Tween 80. The responses evaluated were percent transmittance, pH, and viscosity. Anti-inflammatory activity was assessed in vivo in male mice using a posttest-only control group design. The treatment groups included sodium diclofenac as the positive control (KP), CMC-Na as the negative control (KN), 0.5% red ginger extract (EJM), 0.5% fermented red ginger extract (EFJM), and a nano spray gel containing 0.5% fermented red ginger extract (SNSG) Result: The optimized formulation achieved a desirability value of 0.948. The formulation exhibited a pH of 6.0 ± 0.06, transmittance of 99.1 ± 0.12%, and viscosity of 537.7 ± 2.08 mPa·s. Particle size analysis showed an average particle size of 14.35 nm and a PDI of 0.1012, confirming the successful development of a homogeneous nanodispersion system. The nano spray gel containing fermented red ginger extract demonstrated notable anti-inflammatory activity, with an AUC value of 0.0145 and an AIA of 80.67% after 1.5 hours of treatment, indicating effective inhibition of inflammation